Novel foods in the European Union: Scientific requirements and challenges of the risk assessment process by the European Food Safety Authority. (November 2020) - Ververis, Ermolaos; Ackerl, Reinhard; Azzollini, Domenico; Colombo, Paolo Angelo; de Sesmaisons, Agnès; Dumas, Céline; Fernandez-Dumont, Antonio; Ferreira da Costa, Lucien; Germini, Andrea; Goumperis, Tilemachos; Kouloura, Eirini; Matijevic, Leonard; et al.
Graphical abstract: Highlights: EFSA performs risk assessment of novel foods in the European Union. Novel food applications have notably increased during the last 2 years due to legislative changes. The nature and complexity of novel foods may impact the data required for risk assessment. A novel food application should be prepared considering the entire body of knowledge available on the novel food. Abstract: The European Food Safety Authority (EFSA) has been involved in the risk assessment of novel foods since 2003. The implementation of the current novel food regulation in 2018 rendered EFSA the sole entity of the European Union responsible for such safety evaluations. The risk assessment is based on the data submitted by applicants in line with the scientific requirements described in the respective EFSA guidance document. The present work aims to elaborate on the rationale behind the scientific questions raised during the risk assessment of novel foods, with a focus on complex mixtures and whole foods. Novel foods received by EFSA in 2003–2019 were screened and clustered by nature and complexity. The requests for additional or supplementary information raised by EFSA during all risk assessments were analyzed for identifying reoccurring issues. In brief, it is shown that applications concern mainly novel foods derived from plants, microorganisms, fungi, algae, and animals. A plethora of requests relates to the production process, the compositional characterization of the novel food, and the evaluation of the product's toxicological profile. Recurring issues related to specific novel food categories were noted. The heterogeneous nature and the variable complexity of novel foods emphasize the challenge to tailor aspects of the evaluation approach to the characteristics of each individual product. Importantly, the scientific requirements for novel food applications set by EFSA are interrelated, and only a rigorous and cross-cutting approach adopted by the applicants when preparing the respective application dossiers can lead to scientifically sound dossiers. This is the first time that an in-depth analysis of the experience gained by EFSA in the risk assessment of novel foods and of the reasoning behind the most frequent scientific requests by EFSA to applicants is made.